¿Los medios probatorios calificados como extemporáneos en base a lo previsto en los artículos 141° y 148° del código tributario deben ser valorados en el proceso contencioso administrativo? - Iraita Villasante, Paolo César (2024)
This paper analyzes the problems related to the rules that should be applied during the assessment of the evidence presented at the Judicial Tax Court when those means of proof where not accepted by the Administrative Tax Court in a decision submitted under the Articles 141° and 148° of the Peruvian Tax Code. For that purpose, we investigate the relevance of the rules provided by Articles 141° and 148° of the Peruvian Tax Code, which contribute to give legitimacy and effectiveness to the collaboration duty that taxpayers must accomplish during the tax audits conducted by the Peruvian Tax Administration, which constitutes the basis of the tax controversy discussed whereas at the administrative level or at the judicial process. Furthermore, we raise awareness of the characteristics that are inherent to the Contentious - Administrative Process, governed by Law N° 27184, in order to discover if the reference to the Full Jurisdiction Principle justifies the different treatment that could be applied to the referred extemporaneous evidence at the judicial instance in comparison to the rules that are mandatory applied at the Administrative Tax Court. Finally, we suggest to modify Law N° 27584 in order to establish uniform rules related to the assessment of the extemporaneous evidence, regardless if the tax controversy is legally discussed at the administrative or the judicial court.